Kant's Religion within the boundaries of mere reason : a critical guide - Michalson, Gordon E., 1948- (Cambridge University Press, 2014)
This volume provides a synoptic view of Kant's major work of religious thought.
Keywords: Kant, Immanuel, -- 1724-1804. -- Religion innerhalb der Grenzen der blossen Vernunft.; Religion innerhalb der Grenzen der blossen Vernunft (Kant, Immanuel); Religion -- Philosophy.; Good and evil.; Religion.; Religion -- Philosophie.; religion (discipline); RELIGION -- Philosophy.; Good and evil; Religion; Religion -- Philosophy